Kepuasan Hidup Wanita Lansia: Studi Kasus Pada Tiga Subjek Di Provinsi Lampung - Anggraini, Elen Dea; Eska Prawisudawati Ulpa; Annisa Fitriani (Universitas Darul Ulum, 2025)
Life satisfaction reflects an individual's subjective well-being, influenced by health, social support, economy and culture. For older women in Lampung, culture plays a key role in shaping their life experiences, particularly in family relationships and the role as custodians of tradition. Lampung culture, with its Pepadun and Saibatin customary systems, emphasizes the value of collectivity, respect for age, and the role of close-knit families. However, modernization and urbanization have led to social changes that have shifted the social roles of older women, limited economic access, and decision-making. This study aims to analyze the influence of Lampung culture on the life satisfaction of elderly women, focusing on compassion, acceptance of change, and life achievement. This study used a qualitative approach with phenomenological methods to analyze the influence of Lampung culture on the life satisfaction of elderly women, focusing on affection, acceptance of change, and life achievement. The results showed that family support is very important in increasing life satisfaction. All three research subjects felt satisfied with their lives thanks to family affection, despite facing physical and social challenges. They also felt proud of their achievements, especially in maintaining traditions and raising children. Overall, Lampung culture, with values such as Piil Pesenggiri, provides a strong foundation for the psychological well-being of older women. Family support and acceptance of social change are important factors in improving the life satisfaction of older women in Lampung.